INFLUENCE OF N-ACETYLCYSTEINE AND LOSARTAN ON MODULATION OF CYTOPROTECTIVE AUTOPHAGY IN MYOCARDIUM OF RATS WITH EXPERIMENTAL TYPE 1 DIABETES MELLITUS (FOR ELECTRONIC MICROSCOPY EXPLANATION) - I.M. Sytnyk; L.O. Stechenko; O.I. Krivosheeva; L.V. Natrus; M.V. Khaitovych (Bogomolets National Medical University, 2017)
The purpose of the research work is to study the features of the autophagy in case of the streptozotocin-induced type 1 diabetes mellitus and its changes in the application of different pharmacological schemes, such as N-acetylcysteine (NAC) and losartan (LOS). Materials and methods. Type 1 diabetes mellitus (DM1) was induced by intraperitoneal injection of streptozotocin (STZ) at the dose of 50 mg/kg. Animals were randomly divided into 5 groups: Control (intact rats); DM1 (untreated diabetic control rats supplemented with 0.9% normal saline per os); NAC (diabetic rats treated with N-acetylcysteine at a dose 1.5g/kg per os); LOS (diabetic rats treated with losartan at a dose 20mg/kg per os as reference drug); NAC+LOS ( diabetic rats treated with combination of NAC and LOS per os). The portions of the left ventricle myocardium were the material of the electromicroscopical research studies. Results. Metabolical type structural changes (changes in mitochondria of endoplasmatic reticulum, lysosome and autophagosome) were found out in the cardiac cells of rats with the STZ DM1. In the NAC experimental group, ultrastructural features of upregulation of the protein secretion in the cardiac cells were found out and directed against newly created myofibrilla in the setting of the hypertrophy of the metabolic type cell organelle; the autophagy processes started to work. In the LOS experimental group, major contraction damages of cardiomyocytes were found out along with decreasing number of autophagosomes: disorganization of mitochondria, anastalsis of myofibrilla and its localized lysis, albuminous degeneration, localized fractional necrosis of cardiomyocytes' cytoplasm. In the NAC+LOS experimental group, the number of the autophagosome also considerably decreased; the cardiomyocytes' burned-out changes and disruption of microcirculation were found out. Summary. Due to the data of the electromicroscopical research study, NAC was found out as more effective restitution of the autophagy cytoprotective system, it was caused by its modulating action on oxidative stress- autophagy target that can become a new treatment strategy in searching of selective cardioprotective drugs for the patients with diabetic cardiomyopathy.